1982
DOI: 10.1093/infdis/145.2.715
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Rabies Virus in the Saliva of Dogs

Abstract: Thirty-nine dogs were injected intramuscularly with either an Ethiopian strain or a Mexican strain of rabies virus. The excretion of rabies virus in the saliva was studied before and during illness. Nine of 17 dogs that died after injection with the Ethiopian strain had virus in the submaxillary glands. Four of these dogs excreted virus in the saliva up to 13 days before signs of disease were observed. Sixteen of 22 dogs that died after injection with the Mexican strain had virus in the submaxillary glands. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 5 publications
3
34
0
Order By: Relevance
“…Fekadu and co-workers demonstrated that dogs infected with the "Ethiopian strain" could excrete virus in saliva for a long time without showing any signs of disease (208,293,294). Experimentally, this strain appeared to produce the carrier state, whereas a rabies isolate from a Mexican dog did not (203). Similar findings have been reported from India (210).…”
Section: Variations In the Pathogenesissupporting
confidence: 86%
See 1 more Smart Citation
“…Fekadu and co-workers demonstrated that dogs infected with the "Ethiopian strain" could excrete virus in saliva for a long time without showing any signs of disease (208,293,294). Experimentally, this strain appeared to produce the carrier state, whereas a rabies isolate from a Mexican dog did not (203). Similar findings have been reported from India (210).…”
Section: Variations In the Pathogenesissupporting
confidence: 86%
“…Dogs inoculated with a Mex i can i so 1 ate had SMSG wi th vi ra 1 titers rang i ng from 10 1 to 10 7 . 3 MICLD50 /g (203). For the practical aspects of assessing the danger of exposure, any of the above species can have very high titers of virus in saliva and it would seem to be very difficult to determine the degree of risk by determining differences in viral titers in salivary glands.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…The size of the dog population in the project area must be rates still need to be recorded, and spatial and temporal patterns await thorough analysis. From the few relatively detailed descriptions available [18][19][20][21] one gets the impression that dog rabies is highly enzootic, with only moderate fluctuations of prevalence. The disease is spread from dog to dog by bite, and other routes of infection appear to have little importance.…”
Section: Control Of Enzootic Dog Rabiesmentioning
confidence: 99%
“…Therefore, it is assumed that as the incubation period of rabies virus gets shortened, there will not be sufficient time for development of Negri bodies. Fekadu et al stated that development of Negri bodies is related to the time length, a rabid victim stays alive after exhibiting the signs of rabies [7].…”
Section: Discussionmentioning
confidence: 99%